Solar cells conversion efficiency enhancement techniques - Prażmowska, Joanna; Paszkiewicz, Regina; Korbutowicz, Ryszard; Wośko, Mateusz; Tłaczała, Marek (Oficyna Wydawnicza Politechniki Wrocławskiej, 2007)
In order to enhance the conversion efficiency of GaAs p-i-n solar cells GaAs/AlxGa1–xAs QW within intrinsic region or gradation of Al fraction of AlxGa1–xAs emitter and base region were applied. The influence of AlAs Bragg reflectors on the performance of MQWSC was studied theoretically by using SimWindows software.
Optica Applicata, Vol. 37, 2007, nr 1-2, s. 93-99
Keywords: optyka; quantum well solar cells; graded solar cells; Bragg reflectors; conversion efficiency; SimWindows